2006
DOI: 10.1021/es060823+
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Loading Rate on the Fate of Mercury in Littoral Mesocosms

Abstract: The effects of changes in atmospheric mercury (Hg) deposition on aquatic ecosystems are poorly understood. In this study, we examined the biogeochemical cycling of Hg in littoral mesocosms receiving different loading rates (7-107 microg Hg m(-2) year(-1)). We added a 202Hg-enriched preparation to differentiate the experimentally added Hg from the ambient Hg in the environment. This approach allowed us to follow the distribution and methylation of the isotopically enriched ("spike") Hg in the mesocosms. Within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 36 publications
7
36
0
1
Order By: Relevance
“…The calculation of relevant numbers for these parameters requires that the quantities of MeHg formed and bioaccumulated in the mesocosms are proportional to the amount of added tracer. This has been convincingly demonstrated in previous lake mesocosm experiments where the loading rate of a Hg II tracer to the water column was varied more than one order of magnitude 38,47 and yielded proportional amounts of formed and bioaccumulated MeHg. We used the BSAF to quantify bioaccumulation in order to facilitate a transparent comparison of accumulation of the different tracers in all the biota species (benthic invertebrates, amphipods and plankton).…”
Section: Discussionsupporting
confidence: 72%
“…The calculation of relevant numbers for these parameters requires that the quantities of MeHg formed and bioaccumulated in the mesocosms are proportional to the amount of added tracer. This has been convincingly demonstrated in previous lake mesocosm experiments where the loading rate of a Hg II tracer to the water column was varied more than one order of magnitude 38,47 and yielded proportional amounts of formed and bioaccumulated MeHg. We used the BSAF to quantify bioaccumulation in order to facilitate a transparent comparison of accumulation of the different tracers in all the biota species (benthic invertebrates, amphipods and plankton).…”
Section: Discussionsupporting
confidence: 72%
“…3). Previous studies have shown that, on the short term, there is a proportional response of rates of production (24,25) and bioaccumulation (26) of new methylmercury to new additions of inorganic mercury. However, when new mercury is added to a system that already contains older inorganic mercury, both the new and older mercury contribute to methylation (although not necessarily equally), so on the short term the overall rate of mercury methylation (new ϩ old) does not respond in direct proportion to the amount of new mercury added.…”
Section: Resultsmentioning
confidence: 99%
“…4). By comparison, Butler et al (2008) , and mosquitoes (Hammerschmidt and Fitzgerald 2005), and directly with MeHg production (Orihel et al 2006;). reported that Hg wet deposition between 1992 and 2004 accounted for about two-thirds of Hg variation in largemouth bass between 1990 and 1995. suggested that reductions in anthropogenic Hg emissions could result in proportionally lower levels of Hg concentrations in fish, but that the magnitude and timing of the response are unclear.…”
Section: Comparison To Wet Depositionmentioning
confidence: 99%